2023
DOI: 10.3389/fendo.2022.1028191
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone stimulates lipolysis in mice but not in adipose tissue or adipocyte culture

Abstract: The inhibitory effect of growth hormone (GH) on adipose tissue growth and the stimulatory effect of GH on lipolysis are well known, but the mechanisms underlying these effects are not completely understood. In this study, we revisited the effects of GH on adipose tissue growth and lipolysis in the lit/lit mouse model. The lit/lit mice are GH deficient because of a mutation in the GH releasing hormone receptor gene. We found that the lit/lit mice had more subcutaneous fat and larger adipocytes than their hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The inhibitory effect of GH on adipose tissue growth has been demonstrated by multiple studies (4,52,53), but the underlying mechanism is not fully understood. In a previous study, we found that the GH-deficient lit/lit mice were growth retarded overall but accumulated more subcutaneous fat compared to the GH-normal lit/+ mice at the same age (39). These phenotypes of the GHdeficient lit/lit mice are consistent with those of GHR-null mice (54) and similar to the body weight and body composition changes in GH-deficient humans (53,55).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The inhibitory effect of GH on adipose tissue growth has been demonstrated by multiple studies (4,52,53), but the underlying mechanism is not fully understood. In a previous study, we found that the GH-deficient lit/lit mice were growth retarded overall but accumulated more subcutaneous fat compared to the GH-normal lit/+ mice at the same age (39). These phenotypes of the GHdeficient lit/lit mice are consistent with those of GHR-null mice (54) and similar to the body weight and body composition changes in GH-deficient humans (53,55).…”
Section: Discussionsupporting
confidence: 69%
“…The lit/lit mice carry a mutation that disable the GH releasing hormone receptor (ghrhr) gene, and as such, mice homozygous for the mutation (lit/lit) are deficient in GH and smaller than wild-type or lit/+ mice (37,38). In a previous study, we found that the lit/lit mice had more subcutaneous fat than the lit/+ mice despite being much smaller than the latter (39). In this study, we found that the lit/lit mice accumulated more preadipocytes in subcutaneous fat but that terminal differentiation of preadipocytes from the lit/lit mice into adipocytes was not affected by GH in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones regulate serum levels of cholesterol by stimulating cholesterol biosynthesis through inducing HMGCR, cholesterol export [primarily as lowdensity lipoprotein (LDL) and very LDL (VLDL)], reverse transport from peripheral tissues, hepatic reuptake via LDL receptors (LDLRs), and cholesterol conversion into bile acids in the liver [170,171]. The past and updated reviews are recommended for the direct and indirect effects of thyroid hormone on mitochondria [172][173][174][175][176][177]. The sympathetic nervous system stimulates hepatic gluconeogenesis, whereas the parasympathetic system does not.…”
Section: Response To Hormonal and Neurogenic Regulationmentioning
confidence: 99%